Caracterização morfoagronômica da coleção de germoplasma de jatobá-do-cerrado (Hymenaea stigonocarpa Mart. ex Hayne) da UFG - Gonzaga, Lamartine Nogueira (2017)
Hymenaea stigonocarpa is classified as a priority for research and sustainable exploitation, with potential for fruit production. There is a phenotypic variation in the species that allows the distinction of three botanical varieties based on leaf characters. The present study aimed to characterize and evaluate the magnitude and distribution of the genetic variability of a germplasm collection of the species. The experimental material consisted of 336 accessions of 120 maternal families, from 24 subpopulations sampled in the Brazilian Cerrado. Plant height, stem diameter, number of branches and number of leaves were measured. Later, they were measured the morpho-agronomic variables: leaf length, leaf width, petiole length, petile diameter, leaf angle, leaflets angle and chlorophyll index. Growth dynamics and analysis of variance were performed to estimate genetic and statistical parameters and selection gain, for growth traits. Data from 113 progenies were used to estimate phenotypic and genetic correlation coefficients. It was also determined the relative importance of the variables for genetic divergence. The dynamics of growth were different in different periods, which is attributed to the formation of the root system in the initial phase of growth. The effects of progeny and subpopulation explain considerably part of the total variation, being significant between and, predominantly, not significant within subpopulations for the growth variables. The morpho-agronomic traits showed significant variation within subpopulations. The cluster analysis showed the formation of two distinct groups which corroborates a population study previously carried out with molecular markers. There is significant variation between subpopulations for growth trais, with possibility of selection for these variables. Based on morphological agronomic variables, the genetic variability is structured among subpopulations. Plants with high growth rates in height have a high growth rate of stem diameter. The variables petiole length (CP), petiole diameter (DP) and final stem diameter (DF) were the most determinant in the discrimination of accessions.